STRATEGI MEMBIDIK KETERSEDIAAN AUDIENS DALAM INDUSTRI TELEVISI (Studi Deskriptif Tayangan Film India ANTV) - Rubiyanto Rubiyanto (Bricolage : Jurnal Magister Ilmu Komunikasi, 2018)
ABSTRACTThe success of ANTV captured the attention of the audience through the Indian Movie show influenced ANTV's position to television in the first rank. The television, which used to be in the last number among rival televisions, tried the first time to broadcast an Indian movie called Mahabharata, which had been successfully aired by TPI in the 1990s. The latest version of the Indian movie gets a great reception from the audience. This article aims to describe ANTV's strategy in the television industry through Indian movie to win the competition. According to Pringle and Starr (2006: 123-125), when planning a program to be aired, the television managers should pay attention to the nine factors, namely (1) Strength or Weakness of Competing Stations, (2) Building Audience Flow, (3) Building Audience Habit, (4) Available Audience, (5) Audience Interest, (6) Advertiser Interest, (7) Budget, (8) Inventory Program, and (9) Local Production Capabilities. The authors limit this study to the available audience and the scheme programing of ANTV. The research method used qualitative descriptive with data collection technique, consist of interview, observation, and documentation. Based on the results of research and data analysis can be concluded that the Indian movie impressions in accordance with the ANTV audience target, so this show succeeded in drawing the attention of the audience, and became the top program. Scheme of ANTV programs illustrate the suitability of the broadcast time slot division and the available audience. These two conclusions refer to Pringle and Starr's thoughts. ANTV's strategy review to win the competition in the television industry opens up a new idea. In this research describe not only on-air programs but also strengthened by off-air program.Keywords: Program, Indian Movie, ANTV, Available AudienceABSTRAKKeberhasilan ANTV merebut perhatian audiens melalui tayangan Film India memengaruhi posisi ANTV menjadi televisi di peringkat pertama. Televisi yang tadinya berada di nomor buncit di antara televisi saingan, mencoba kali pertama menayangkan film India berjudul Mahabharata, yang pernah sukses ditayangkan TPI tahun 1990-an. Versi terbaru film India ini mendapat sambutan luar biasa dari audiens. Artikel ini bertujuan mendeskripsikan strategi ANTV dalam industri televisi melalui tayangan film India untuk memenangkan persaingan. Menurut Pringle dan Starr (2006:123-125), ketika merencanakan sebuah program yang akan ditayangkan hendaknya pengelola televisi memperhatikan Sembilan faktor, yaitu: (1) Strength or Weakness of Competing Stations, (2) Building Audience Flow, (3) Building Audience Habit, (4) Available Audience, (5) Audience Interest, (6) Advertiser Interest, (7) Budget, (8) Program Inventory, dan (9) Local Production Capabilities. Penulis membatasi kajian pada ketersediaan audiens (available audience) dikaitkan dengan daypart pada pola pemrograman ANTV. Metode penelitian menggunakan kualitatif deskriptif dengan teknik pengumpulan data, terdiri dari wawancara, observasi, dan dokumentasi. Berdasarkan hasil penelitian dan analisis data dapat disimpulkan bahwa tayangan film India sesuai dengan target audiens yang diusung ANTV, sehingga tayangan iniberhasil menyedot perhatian penonton, dan menjadi program unggulan. Penjadwalan program acara di ANTV menggambarkan kesesuaian pembagian slot waktu siaran dan ketersediaan audiens. Kedua simpulan ini sesuai dengan pemikiran Pringle dan Starr. Kajian strategi ANTV untuk memenangkan persaingan dalam industri televisi ini membuka sebuah pemikiran baru, yaitu gambaran strategi yang tidak hanya terpaku pada tayangan on-air, namun juga diperkuat dengan kemasan program off-air.Kata kunci: Program, Film India, ANTV, Ketersediaan Audiens